Colorimetric detection of Maize chlorotic mottle virus by reverse transcription loop-mediated isothermal amplification (RT-LAMP) with hydroxynapthol blue dye. Issue 1 (21st December 2015) - Liu, Zhanmin; Xia, Xueying; Yang, Cuiyun; Huang, Junyi
Abstract : Maize chlorotic mottle virus causes corn lethal necrosis disease, and can be transmitted via infected maize seeds. A colorimetric assay for the detection of Maize chlorotic mottle virus was developed which utilises RT-LAMP and hydroxynapthol blue dye (HNB). Abstract : Maize chlorotic mottle virus causes corn lethal necrosis disease, and can be transmitted via infected maize seeds. It remains a challenge to detect this virus to prevent its introduction, infection and wide transmission in fields. For this purpose, a colorimetric assay for the detection of Maize chlorotic mottle virus was developed, which utilises RT-LAMP and hydroxynapthol blue dye (HNB). The reaction was performed for amplification in one step in a single tube at the optimum conditions (64 °C for 60 min, 150 μM HNB and 2 mM MgSO4 ). Samples infected with MCMV developed a characteristic sky blue color after the reaction but those uninfected with MCMV or infected with other plant pathogenic viruses did not. The results of the HNB staining method were reconfirmed through gel electrophoresis of the RT-LAMP products. The sensitivity of this assay was 4.8 pg μl −1 of RNA of Maize chlorotic mottle virus per reaction, which was approximately 10-fold higher sensitivity over a conventional RT-PCR test. The results indicate that this assay is highly species-specific, simple, low-cost, and visual for easy detection of Maize chlorotic mottle virus in plant tissues. Therefore, colorimetric detection of Maize chlorotic mottle virus is a potentially useful tool for middle or small-scale corporations and entry-exit inspection and quarantine bureaus to detect maize seeds or plant tissues infected with Maize chlorotic mottle virus .